Effect of Silage Additives on Rumen Fermentation Pattern and Economics of Wheat Straw and Pasture Hay-based Green Maize Silage - Y Belim, Saman; H Savsani, Harish; G Kansagara, Yash; D Odedara, Mulraj; R Chavda, Mitesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The investigation was conducted to study the effect of Lactobacillus bacterial inoculants (Lactobacillus fermentum, Lactobacillus plantarum) and xylanase in maize silage along with different dry fodders like wheat straw and seasonal pasture hay and to evaluate rumen fermentation pattern, and the cost effectiveness of additives. Different silages were prepared using green maize fodder and wheat straw (WS) and pasture hay (PH) separately in the proportion of 10:0 & 7:3 ratio in plastic jar of 3 kg capacity by adding common salt @ 0.5%, urea @ 1% and molasses @ 1.5% in each silage with 9 different treatments, viz., Control (green maize alone), WS, X, LF, LPLF, PH, XPH, LFPH and LPLFPH. Xylanase, LP and LF were used @ 1500 IU/g, 1 x 106 cfu/g and 2 x 106 cfu/g, respectively. All silages were evaluated in terms of their in vitro rumen fermentation parameters on 45 days of ensiling. Xylanase inoculated maize + wheat straw and maize + pasture hay silage significantly improved TVFA, total gas production, IVDMD, IVOMD and PF. LPLF added maize + WS silage significantly increased in vitro rumen ammonia nitrogen and total nitrogen content. Thus, it is concluded that Xylanase can be used as cost effective additive in silage production for maximum nutrient utilisation and overall economic benefits.